2023
DOI: 10.34133/research.0023
|View full text |Cite
|
Sign up to set email alerts
|

Rotating Surfaces Promote the Shedding of Droplets

Abstract: Achieving rapid shedding of droplets from solid surfaces has received substantial attention because of its diverse applications. Previous studies have focused on minimizing contact times of liquid droplets interacting with stationary surfaces, yet little consideration has been given to that of moving surfaces. Here, we report a different scenario: A water droplet rapidly detaches from micro/nanotextured rotating surfaces in an intriguing doughnut shape, contributing to about 40% contact time reduction compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…In addition, other works, such as designing parallel macro ridges , or adjusting the eccentricity and the size ratio between droplet and ridge, have also been inspired and conducted. Recently, Tao et al found that on a rotating surface, the central film of an impacting droplet could easily break due to the centrifugal force, which reduced the recoiling distance. The droplet could rebound from the surface as a doughnut-like shape, shortening the contact time by 40%.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other works, such as designing parallel macro ridges , or adjusting the eccentricity and the size ratio between droplet and ridge, have also been inspired and conducted. Recently, Tao et al found that on a rotating surface, the central film of an impacting droplet could easily break due to the centrifugal force, which reduced the recoiling distance. The droplet could rebound from the surface as a doughnut-like shape, shortening the contact time by 40%.…”
Section: Introductionmentioning
confidence: 99%
“…Capillary force enables the long-distance transport of liquids (figure 5(a)) [69]. Recently, the involvement of external forces in microfluidics is attracting more and more attention [70,71]. For example, electric field forces have been added to the microfluidic devices, including electrically induced wetting, liquid flow, and droplet motion enabled by charges [72,73] (figure 5(b)).…”
Section: Driving Force and Hydrodynamics Inside Microchannelsmentioning
confidence: 99%
“…7 There have been several reports of contact-time reduction by engineering surfaces or substrates. Droplet impact on various engineered surfaces shows distinct mechanisms of contact-time reduction, such as pancake bouncing, 8,9 doughnut bouncing, 10 nonaxisymmetric recoil, 11 and film rupture. 12 Liquid marble (LM), a hydrophobic powder-coated liquid drop, has gained considerable interest in recent years due to its wide range of applications in compound lenses, 13 smart reactors for chemical and biological synthesis, 14,15 logic gates, 16,17 stimuli-responsive adhesive, 18 and sensors.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several reports of contact‐time reduction by engineering surfaces or substrates. Droplet impact on various engineered surfaces shows distinct mechanisms of contact‐time reduction, such as pancake bouncing, 8,9 doughnut bouncing, 10 nonaxisymmetric recoil, 11 and film rupture 12 …”
Section: Introductionmentioning
confidence: 99%